Student Moods Before and After Body Expression and Dance Assessments. Gender Perspective - Mateu, Mercè; Garcías, Silvia; Spadafora, Luciana; Andrés, Ana; Febrer, Eulàlia (Frontiers in Psychology, 2021)
Body expression and dance are activities that contribute to the integral well-being of people. In an educational context, the process of evaluating them implies variations in the moods of the students. This study explains the states of mind that students perceive before and after the evaluation of a practice in the subject of Body expression and dance through choreographies, previously rehearsed, and presented to the rest of the class in a specific session. Our main interest was the obtention of information on the states of mind of the students prior to the evaluation of their choreography, as well as after the evaluation test. The study design consisted of two phases: two different choreographies separated by an interval of two months. The students were asked about their moods before and after performing their choreographies, which were evaluated. The participants, 160 in total, 35 women (20.5%) and 132 men (79.5%), aged between 18 and 22 years, filled out the POMS Profile of Mood States questionnaire, before and after the evaluation of their choreography. Differences were found in the tension-anxiety, vigor-activity, fatigue-immobility scales and the total mood score (PGEA). In all of them, except for the fatigue-immobility scale, there was a decrease in the scores after the performance, compared to the scores before it. We conclude that the practical evaluation of the subject through choreography modifies the states of mind of the students, favoring their well-being after its execution, which is why evaluation through practice is considered a positive element in the educational process.